Pengaruh Pemakaian Jilbab Terhadap Pembentukan Kepribadian Siswi - Ahmad Adnan; Muslichah Ninik (STID DI AL-HIKMAH, 2017)
The background of this study is the change in the personality of students of SMK Bakti 17 after using the veil. Student who uses the veil has a personality that is better than the girls who do not wear veils. The purpose of this study was to determine the effect of the use of the veil on the personality SMK Bakti 17 Cipedak, Jagakara, South Jakarta. The research object is a student in SMK Bakti veil users 17 Cipedak South Jakarta. The research methodology using quantitative descriptive approach. The conclusion was that there is a positive effect of the use of the veil of the student's personality. This is indicated by the discipline of time, worship, cleanliness, attitude to life (patient and focused), and improvement of morals by following school Rohis.